Rancang Bangun Sistem Informasi Penjualan dan Manajemen Stok Berbasis Web pada UMKM Manufaktur BAM Assesoris - Nirmawati; Farizi Ilham; Janu Sari; Saarah Nabilah Tsabitah (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
BAM Assesoris is a helmet manufacturing small and medium enterprise located in Tangerang. In its daily operations, the company has relied on manual recording using notebooks and WhatsApp communication to manage inventory and sales, leading to frequent data entry errors, delayed reporting, and difficulties in tracking transaction history and stock data. The complexity is further increased by the separate management of stock and sales between two parties operating within the same production line, particularly in raw material borrowing activities that have not been systematically documented, as well as manual raw material requirement calculations that risk undetected material shortages. This study aims to design and develop a web-based sales and stock management information system capable of integrating sales data management, inventory management, raw material requirement calculations, and raw material borrowing transaction records in an automated and structured manner. The system was developed using the prototype method, with data collected through direct interviews, field observations, and literature reviews. The system was built using web-based technology with role-based access control for three types of users: owner, admin, and customer. The results show that the developed system successfully replaces manual processes, improves recording efficiency and accuracy, and facilitates better coordination among stakeholders in managing BAM Assesoris operations.